1997
DOI: 10.7326/0003-4819-126-7-199704010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Expression of Disease in Families That Have Mutations in the 5′ Region of the Adenomatous Polyposis Coli Gene

Abstract: Families with adenomatous polyposis that have proximal 5' mutations of the adenomatous polyposis coli gene are more likely to have a heterogeneous phenotype with delayed development of colonic polyposis and colorectal cancer than are families with distal 5' mutations of the gene. Management should include genotyping of patients who are at risk, colonoscopic surveillance of genotypically positive persons, and prophylactic colectomy if several adenomas are found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 0 publications
6
58
0
1
Order By: Relevance
“…We found that mutation in the 3' end of the APC gene was associated with intrapedigree variability of both colonic and extracolonic 15 Analogous to the boundary for phenotypic manifestations of mutations at the 5' end of the APC gene, a boundary at the 3' end of the gene at codon 1596 separates families with variable intrapedigree phenotype from classic FAP phenotype.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…We found that mutation in the 3' end of the APC gene was associated with intrapedigree variability of both colonic and extracolonic 15 Analogous to the boundary for phenotypic manifestations of mutations at the 5' end of the APC gene, a boundary at the 3' end of the gene at codon 1596 separates families with variable intrapedigree phenotype from classic FAP phenotype.…”
Section: Discussionmentioning
confidence: 77%
“…29 This is consistent with the delayed development of colorectal cancer observed in AAPC families with proximal 5' mutations. 15 Nevertheless, the cumulative risk of colorectal cancer seems to reach 100% in attenuated adenomatous polyposis caused by 5' mutation of the APC gene, 15 and 3' families may follow a similar course. 19 Extracolonic manifestations characteristic of FAP also showed intrafamilial variation and did not correlate with phenotypic expression of colorectal polyposis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who have frameshift mutations between codons 1250 and 1330 develop more than 5000 polyps, whereas mutations outside this region generally leads to less than 2000 polyps and milder disease (Nagase et al 1992b;Friedl et al 1996). Families with mutations located toward the 5' end of codon 158 are more likely to have heterogeneous features including delayed development of colonic polyposis ■ "*■ and colorectal cancer than families with more distal 5'mutations in the gene (Giardiello et al 1997). Other mutations such as a frameshift mutation and a termination at codons 1862 and 1987 have been associated with greater variability in the number of colorectal adenomas, and mutations at codon 1309 results in thousands of adenomas at a young age and earlier death (Caspari et al 1995;Gaytheretal.…”
Section: Mismatch Repair Genes Hmsh2 and Hmlhlmentioning
confidence: 99%
“…3 Traditional diagnostic methods can identify APC mutations in 50 to 90% of patients with typical FAP and in 20 to 30% of patients with AFAP, depending on the patients examined and the methods used (Solomon C, Burt RW: APC-Associated Polyposis Conditions. GeneReviews: http://www.geneclinics.org., accessed October 21,2005). 4 -7 Recently, large genomic deletions encompassing one to several exons or even the entire APC gene have been identified by use of multiplex ligation-dependent probe amplification (MLPA) in ϳ7 to 12% of all patients with typical FAP.…”
mentioning
confidence: 99%